Internet broadband for an inclusive digital society (UN New YorkUS, 2013)
Presents the findings of the intersessional panel meeting hedl in Lima, Peru, from 7 - 9 January 2013. Reviews the international status of broadband and proposes a set of policies to promote broadband development in developing countries.
Keywords: TELECOMMUNICATIONS NETWORKS